FUNCTIONAL COATINGS BY TERNARY COBALT BASED ALLOYS FOR THE AUTUMOBILE INDUSTRY - Nenastіna, T.; Hapon, Ju.; Glushkova, M.; Sakhnenko, N.; Ved’, M.; Ненастина, Т. А.; Гапон, Ю. К.; Глушкова, М. А.; Сахненко, Н. Д.; Ведь, М. В.; Ненастіна, Т. О.; Глушкова, М. O.; et al. (Харьковский национальный автомобильно-дорожный университет, 2015)
The environmentally friendly and resource-saving technologies for producing multifunctional coatings based on cobalt and silver alloys with refractory metals are proposed. The catalytic activity testing results of binary and ternary alloys based on cobalt in the carbon monoxide oxidation reaction in carbon dioxide were analyzed. It was revealed that there is on improvement of functional properties of galvanic alloys when the content of tungsten and molybdenum is within the range of 10–30 wt. %
ФУНКЦІОНАЛЬНІ ПОКРИТТЯ ТЕРНАРНИМИ СПЛАВАМИ КОБАЛЬТУ ДЛЯ АВТОМОБІЛЬНОЇ ПРОМИСЛОВОСТІ
ФУНКЦИОНАЛЬНЫЕ ПОКРЫТИЯ ТЕРНАРНЫМИ СПЛАВАМИ КОБАЛЬТА ДЛЯ АВТОМОБИЛЬНОЙ ПРОМЫШЛЕННОСТИ
Keywords: citrate-pyrophosphate electrolyte; cobalt-molybdenum-tungsten (silver) alloy; corrosion resistance; catalytic activity; electrolysis; цитратно-пирофосфатный электролит; сплав кобальт–молибден–вольфрам (серебро); коррозионная стойкость; каталитическая активность; электролиз; цитратно-пірофосфатний електроліт; сплав кобальт–молібден–вольфрам (срібло); корозійна стійкість; каталітична активність; електроліз; 621.35